Synergistic Cu/Pd Catalysis for Enantioselective Allylic Alkylation of Aldimine Esters: Access to α, α‐Disubstituted α‐Amino Acids. (23rd August 2017) - Wei, Liang; Xu, Shi‐Ming; Zhu, Qiao; Che, Chao; Wang, Chun‐Jiang
Abstract: An unprecedented enantioselective allylic alkylation of readily available aldimine esters has been developed, and is catalyzed by a synergistic Cu/Pd catalyst system. This strategy provides facile access to nonproteinogenic α, α‐disubstituted α‐amino acids in high yield with excellent enantioselectivity. The more challenging double allylic alkylation of glycinate‐derived imine esters was also realized. Furthermore, this methodology was applied for the construction of the key intermediate of PLG peptidomimetics.